Pelatihan Penyusunan Modul Ajar di Yayasan Swara Peduli Ceria untuk Meningkatkan Kualitas Pembelajaran dan Kompetensi Pengajar - Arif Rahman Hakim; Muhamad Farhan; M. Tohimin Apriyanto; Napis Napis; Rahmatulloh Rahmatulloh (Pusat Riset dan Inovasi Nasional, 2025)
Sustainable learning should begin with strengthening basic skills such as reading, writing, and arithmetic (calistung). This is heavily influenced by the teaching methods, media, and teaching modules used. Adapting the content into student activities through modules is key to improving the quality of the learning process. In response to this issue, the Community Service Team (PkM) conducted a Training on Preparing Teaching Modules at the Swara Peduli Ceria Foundation, located in Klender, East Jakarta. This training aimed to assist educators at the learning center in developing relevant and impactful teaching modules for children. The activity was held at the Learning Center Hall of the Swara Peduli Ceria Foundation, with 15 participants attending. The training was carried out in five stages: (1) initial preparation, (2) activity presentation, (3) delivery of material, (4) activity evaluation, and (5) follow-up. Participants were given both theoretical materials and practical experience in developing teaching modules. The results showed an improvement in the participants' ability to design teaching modules that were appropriate for the needs of the children at the learning center. The final product, a collaboratively developed teaching module, was considered beneficial and practical for the educators to implement in their lessons. This activity provided a positive impact not only for the participants but also for the quality of learning at the center. The PkM program strengthened the role of higher education institutions in supporting sustainable education for the community. By helping educators in preparing suitable teaching materials and modules, the program contributed to enhancing the learning environment for children, ensuring that the education they receive aligns with their developmental needs. This initiative also highlights the importance of collaboration between universities and local educational institutions in improving education quality and fostering sustainable growth in the community.